Improving the Quality of Products and Services in the Era of Digital Disruption: Challenges and Management Strategies - Rizki Satria, Bill Ma’ruf Budiman; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to analyze the challenges and management strategies needed to improve the quality of products and services in this era. Data analysis was carried out using a qualitative method with data analysis from 3 (three) companies that have successfully adapted to digital disruption. The results of the research from data analysis show that the right management strategy can improve the quality of products and services can help companies remain competitive in a rapidly changing market in the era of Digital Disruption. This research also found that in the era of digital disruption, it has brought major changes in various aspects of business, including in improving the quality of products and services positively and significantly.